Heat treatment of a direct composite resin: influence on flexural strength - Caroline Lumi Miyazaki; Igor Studart Medeiros; Ivone Lima Santana; Jivaldo do Rosário Matos; Leonardo Eloy Rodrigues Filho (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The purpose of this study was to evaluate the flexural strength of a direct composite, for indirect application, that received heat treatment, with or without investment. One indirect composite was used for comparison. For determination of the heat treatment temperature, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were performed, considering the initial weight loss temperature and glass transition temperature (Tg). Then, after photoactivation (600 mW/cm² - 40 s), the specimens (10 x 2 x 2 mm) were heat-treated following these conditions: 170ºC for 5, 10 or 15 min, embedded or not embedded in investment. Flexural strength was assessed as a means to evaluate the influence of different heat treatment periods and investment embedding on mechanical properties. The data were analyzed by ANOVA and Tukey's test (α = 0.05). TGA showed an initial weight loss temperature of 180ºC and DSC showed a Tg value of 157°C. Heat treatment was conducted in an oven (Flli Manfredi, Italy), after 37°C storage for 48 h. Flexural strength was evaluated after 120 h at 37°C storage. The results showed that different periods and investment embedding presented similar statistical values. Nevertheless, the direct composite resin with treatments presented higher values (178.7 MPa) compared to the indirect composite resin (146.0 MPa) and the same direct composite submitted to photoactivation only (151.7 MPa). Within the limitations of this study, it could be concluded that the heat treatment increased the flexural strength of the direct composite studied, leading to higher mechanical strength compared to the indirect composite.